Colloidal crystals of compliant microgel beads to study cell migration and mechanosensitivity in 3D. Issue 47 (19th November 2019) - Wagner, Katrin; Girardo, Salvatore; Goswami, Ruchi; Rosso, Gonzalo; Ulbricht, Elke; Müller, Paul; Soteriou, Despina; Träber, Nicole; Guck, Jochen
Abstract : We present a novel 3D colloidal crystal made of polyacrylamide microgel beads with variable stiffness. The beads can be functionalized with ECM proteins and used to study mechanosensing responses of cells to varying stiffness in a 3D context. Abstract : Tissues are defined not only by their biochemical composition, but also by their distinct mechanical properties. It is now widely accepted that cells sense their mechanical environment and respond to it. However, studying the effects of mechanics in in vitro 3D environments is challenging since current 3D hydrogel assays convolve mechanics with gel porosity and adhesion. Here, we present novel colloidal crystals as modular 3D scaffolds where these parameters are principally decoupled by using monodisperse, protein-coated PAAm microgel beads as building blocks, so that variable stiffness regions can be achieved within one 3D colloidal crystal. Characterization of the colloidal crystal and oxygen diffusion simulations suggested the suitability of the scaffold to support cell survival and growth. This was confirmed by live-cell imaging and fibroblast culture over a period of four days. Moreover, we demonstrate unambiguous durotactic fibroblast migration and mechanosensitive neurite outgrowth of dorsal root ganglion neurons in 3D. This modular approach of assembling 3D scaffolds from mechanically and biochemically well-defined building blocks allows the spatial patterning of stiffness decoupled from porosity and adhesion sites in principle and provides a platform to investigate mechanosensitivity in 3D environments approximating tissues in vitro .